Dampak Tragedi Mina Tahun 1990 Terhadap Kebijakan Penyelenggaraan Haji Indonesia - Assodiq, Imam; Madjied, M. Dien (Socio Historica: Journal of Islamic Social History, 2024)
ABSTRACTThis research aims to describe the impact of the 1990 Mina tragedy on Indonesia's Hajj organizing policy in the following Hajj season. The author uses the historical method with a cultural and structural approach, which is a method of approaching problems through the perspective of culture and the structures attached to it. The results of this study show that there was an impact arising from the 1990 Mina tragedy. These impacts are the birth of Siskohat as an administrative system that is faster than the manual data collection system in 1990, the birth of Law No. 17 of 1999 concerning the Implementation of Hajj which was proposed by the PBNU after the 1990 Mina tragedy, the birth of the construction of Hajj Hospitals in four embarkations; Jakarta, Medan, Surabaya, and Ujung Pandang initiated by President Soeharto with financial support from the people of Indonesia and the Government of Saudi Arabia, and the improvement of pilgrims' facilities in Mina, including the construction of a new tunnel and improvement of pilgrims' camp facilities in Mina. The conclusion of this research shows that there is an impact of the 1990 Mina tragedy on Indonesia's Hajj organizing policy in the following Hajj season. This impact can be seen from the improvement of the administrative system, legislation, health facilities in Indonesia and public facilities in Mina.ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan dampak tragedi Mina tahun 1990 terhadap kebijakan penyelenggaraan haji Indonesia pada musim haji berikutnya. Penulis menggunakan metode historis dengan pendekatan kultural dan struktural, yaitu sebuah metode mendekati permasalahan melalui perspektif kebudayaan serta struktur yang melekat padanya. Hasil dari penelitian ini menunjukkan bahwa ada dampak yang muncul dari tragedi Mina tahun 1990. Dampak tersebut ialah lahirnya Siskohat sebagai sistem administrasi yang lebih cepat dibanding sistem pendataan manual tahun 1990, lahirnya Undang-undang No. 17 tahun 1999 tentang Penyelenggaraan Ibadah Haji yang menjadi usulan PBNU pasca tragedi Mina tahun 1990, lahirnya pembangunan RS Haji di empat embarkasi, Jakarta, Medan, Surabaya, dan Ujung Pandang yang diinisiasi oleh Presiden Soeharto dengan dukungan dana dari rakyat dan Arab Saudi, serta perbaikan fasilitas jemaah haji di Mina, termasuk pembangunan terowongan baru serta perbaikan fasilitas perkemahan jemaah haji di Mina. Adapun kesimpulan dari penelitian ini menunjukkan bahwa ada dampak tragedi Mina tahun 1990 terhadap kebijakan penyelenggaraan haji Indonesia pada musim haji setelahnya. Dampak ini terlihat dari perbaikan sistem administrasi, perundang-undangan, fasilitas kesehatan dan fasilitas umum yang ada di Mina.